Novel solid-waste-derived activation materials from phosphogypsum, granulated blast-furnace slag, and calcium carbide slag for sustainable marine construction - Yun-Xin Chen; Gen-Sheng Ren; Hua Tong; Xiao-Dong Yan; Xiao-Gang Song; Yi-Nong Shen (Case Studies in Construction Materials)
The rapid and sustainable expansion demands of marine construction necessitate the development of environmentally adaptive and resource-efficient marine concrete materials. In this study, novel solid-waste-derived activation materials, utilizing phosphogypsum (PG), granulated blast-furnace slag (GGBS), and calcium carbide slag (CS), were developed for sustainable marine construction. Results indicated that the PG-GGBS-CS system not only exhibited an accelerated setting time compared to the PG-GGBS-OPC system, but also demonstrated a substantial strength increase between 7 and 28 days. Notably, a CS content of 5 wt% effectively enhances the strength development, yielding a 28-day strength of 33.5 MPa. Characterization by XRD, TG-DTG, FTIR, SEM-EDS, and MIP confirmed that AFt, C-(A-)S-H gels, and bayerite are the primary reaction products. Excess CS led to a lower reaction degree and porous microstructures, compromising mechanical performance. This work demonstrates the feasibility of large-scale PG utilization and provides a viable route toward the development of fully solid-waste-based marine construction materials.